An evaluation of the B4C formation in sintered ZrB2-SiC ceramic composites at 2100 °C - Dayang Salyani, Abang Mahmod; Amir Azam, Khan; Glandut, Nicolas; Labbé, Jean Claude (Elsevier Ltd, 2018)
The present study was concerned with the high temperature sintering behaviour of zirconium diboride ceramics mixed with fine silicon carbide. Zirconium diboride-silicon carbide (ZrB2-SiC) ceramic composites were pressureless sintered at 2100 °C under flowing argon environment, for a hold time of 150 min. The pressureless sintered ZrB2-SiC pellets were characterized for microstructure and phase analysis. The sintered microstructure was observed through Scanning Electron Microscopy (SEM) embedded with Energy Dispersive Spectroscopy (EDS) and different phases were analyzed through X-ray Diffraction (XRD). The investigation revealed the presence of boron carbide (B4C) within the sintered pellets containing 20 mol.% SiC. The B4C was formed during sintering without the presence of any free carbon as part of initial powder mixture. Possible routes to identify and explain the formation of B4C in the absence of free carbon were discussed. © 2017 Elsevier B.V.